2006
DOI: 10.1158/1535-7163.mct-05-0410
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical activity of ABT-869, a multitargeted receptor tyrosine kinase inhibitor

Abstract: ABT-869 is a structurally novel, receptor tyrosine kinase (RTK) inhibitor that is a potent inhibitor of members of the vascular endothelial growth factor (VEGF) and plateletderived growth factor (PDGF) receptor families (e.g., KDR IC 50 = 4 nmol/L) but has much less activity (IC 50 s > 1 Mmol/L) against unrelated RTKs, soluble tyrosine kinases, or serine/threonine kinases. The inhibition profile of ABT-869 is evident in cellular assays of RTK phosphorylation (IC 50 = 2, 4, and 7 nmol/L for PDGFR-B, KDR, and CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
141
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(156 citation statements)
references
References 52 publications
14
141
0
1
Order By: Relevance
“…[33,[39][40][41][42][43][44][45] Additionally, studies carried out in vitro showed that axitinib did not significantly inhibit other receptor kinases that were tested, including colony-stimulating factor (CSF)-1R, fms-like tyrosine kinase (Flt)-3, fibroblast growth factor receptor (FGFR)-1, ret proto-oncogene (RET), epidermal growth factor receptor (EGFR), and met proto-oncogene encoding hepatocyte growth factor (c-Met). [32] …”
Section: Vascular Endothelial Growth Factor Receptor (Vegfr) Signalinmentioning
confidence: 99%
See 1 more Smart Citation
“…[33,[39][40][41][42][43][44][45] Additionally, studies carried out in vitro showed that axitinib did not significantly inhibit other receptor kinases that were tested, including colony-stimulating factor (CSF)-1R, fms-like tyrosine kinase (Flt)-3, fibroblast growth factor receptor (FGFR)-1, ret proto-oncogene (RET), epidermal growth factor receptor (EGFR), and met proto-oncogene encoding hepatocyte growth factor (c-Met). [32] …”
Section: Vascular Endothelial Growth Factor Receptor (Vegfr) Signalinmentioning
confidence: 99%
“…Data from a phase I two-way crossover study of axitinib alone or coadministered with ketoconazole (a potent CYP3A inhibitor) in healthy volunteers (n = 32) demonstrated that concurrent administration of ketoconazole increased axitinib plasma exposure (AUC „ ) and C max with approximate Relative potency of targeted agents in metastatic renal cell carcinoma (mRCC). [32,33,[39][40][41][42][43][44][45] IC 50 = concentration that produces 50% inhibition; VEGFR = vascular endothelial growth factor receptor. Reproduced from Bellmunt et al, [33] with permission.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Additional novel FLT3 inhibitors in early development include the N-(4-(3-amino-1H-indazol-4yl)phenyl-N1(2-fluoro-5-methylphenyl) urea ABT-869 (Albert et al, 2006;Shankar et al, 2007;Zhou et al, 2008), which is a multitargeted inhibitor with activity toward FLT3, PDGFR, KIT and KDR; the benzimidalzolequinoline CHIR-258 (TKI258; Chiron, Emeryville, CA, USA), which has among its targets FLT3, KIT, FMS, VEGFR and FGFR (Lopes de Menezes et al, 2005) and is a promising antimyeloma drug (Trudel et al, 2005) presently in Phase I clinical trials for multiple myeloma, mixed solid tumors and AML; the hydroxystyrylacrylonitrile LS104 (Kasper et al, 2008), which is in a Phase I clinical trial for patients with refractory/ relapsed hematological malignancies; and AP24534 (Ariad, Cambridge, MA, USA), a multitargeted kinase inhibitor with activity against FLT3, KIT and FGFR (Rivera et al, 2008), and which is in Phase I clinical trials for CML and other hematological malignancies. It is important to note that thus far, no selective FLT3 inhibitor has been developed that would allow the study of FLT3 exclusively as a target.…”
Section: Kinase Inhibitors Under Clinical Investigation For Mutant Flmentioning
confidence: 99%
“…When given in combination with other therapies, linifanib produced at least additive effects. [18,19] Further in vitro studies demonstrated that linifanib at an IC 50 of 10 nmol/L inhibited growth of MV-4-11 cells (human acute myeloid leukemia cell line that expresses FLT3-ITD) and BAF3-ITD cells (murine B-cell line stably transfected with the FLT3-ITD). The drug was also effective against D835V, another FLT3 mutation, with an IC 50 of 100 nmol/L.…”
Section: December 2006mentioning
confidence: 99%